Judge's Consideration of the Surakarta District Court's Divorce Verstek Decision Number 67/Pdt.G/2023/PN Skt - Shabrina, Kania Putri; Setiawati, Diana (Trunojoyo Madura University, 2024)
Marriage is a physical and spiritual bond between prospective male and female partners so that they can live together according to God's will. However, in reality, many couples cannot maintain a domestic relationship due to several reasons that make them divorce using legal channels. This research aims to analyze the judge's decision in determining the verstek decision in a divorce case in the decision case study: Surakarta District Court Number 67/Pdt.G/2023/PN Skt. The research method used uses a normative juridical method, carried out indirectly based on legal materials and several references related to this research. This research uses a library research method by searching for data through books, journal articles, scientific works and websites. The results of this study indicate that The marriage between the plaintiff and the defendant is declared dissolved in accordance with Article 35 of the Marriage Law, and a default judgment in divorce cases can affect various aspects, including marital status, alimony obligations, and the burden of proof in the case. The judge's decision reflects attention to the principles of justice and applicable legal norms.